A comparative study between sedition law in Malaysia and The United States / Amirah Zakaria…[et al.] - Zakaria, Amirah; Sharifiidin, Intan Izureen; Hussin, Siti Muneera; Muhammad, Suria (2010)
The importance of this research is to see the distinctions of the implementation of the law of sedition between Malaysia and the United States. There is a need to analyze the provisions under Malaysian Sedition Act 1948 and Section 2384 of The United States Code: Title 18 relating to the offence of sedition to compare the implementation of law of sedition having between in Malaysia and the United States, "A Comparison Study between Sedition Law in Malaysia and the United States" is the title of this project paper. There are two main objectives to this study which are to analyze the purpose and the scope of the sedition law in both Malaysia and the United States and to critically examine the enforcement and application of the sedition law in Malaysia and the United States. This is due to the fact that although both Malaysia and the United States have provisions regarding sedition offences, there are different restrictions on the freedom of speech and expression imposed especially in terms of its implementation. This research focuses on the sedition law in Malaysia and the United States also in brief to other country such as United Kingdom. The qualitative type of research techniques, a library-based research, and semi-structured interviews were used in carrying out this research.